Titanium and yttrium doped zirconia sintered body
The development of a sintered titania-yttria-zirconia body with specific composition and manufacturing processes addresses the low mechanical strength and poor fracture resistance of conventional zirconia sintered bodies, achieving high transparency and enhanced mechanical properties.
Patent Information
- Application Number
- JP2024193402
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-08-31
- Filing Date
- 2024-11-05
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2044-08-26
AI Technical Summary
Sintered bodies of zirconia with titanium and yttrium solid solutions exhibit high transparency but have low mechanical strength and poor resistance to fracture progression, making them prone to rapid fracture once defects occur.
A sintered titania-yttria-zirconia body with cubic crystal particles containing tetragonal domains, a yttrium content of 3.5 mol% or more and less than 6.0 mol%, and a titanium content of 6.0 mol% or more and 18.5 mol% or less, is developed. This composition is achieved through a manufacturing method involving primary sintering at atmospheric pressure, pressure sintering in a reducing atmosphere, and heat treatment in an oxidizing atmosphere.
The resulting sintered body maintains transparency while significantly enhancing its resistance to fracture progression, achieving a fracture toughness value of 1.5MPa·m0.5 or higher and a three-point bending strength of 280 MPa or more.
Smart Images

Figure 0007670225000004 
Figure 0007670225000005 
Figure 0007670225000006
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sintered body of zirconia containing titanium and yttrium as a solid solution. [Background technology]
[0002] A sintered body made of zirconia in which titanium and yttrium are dissolved and whose crystal phase is composed only of cubic crystals is known as a sintered body having high transparency (Patent Document 1). However, such a sintered body has low mechanical properties. Therefore, improvement of the mechanical properties of such a transparent sintered body has been studied.
[0003] For example, Patent Document 2 discloses that a zirconia sintered body containing titanium and yttrium in a solid solution, which has a three-point bending strength of 255 MPa and is transparent, can be obtained by controlling the crystal grain size of the primary sintered body to be subjected to hot isostatic pressing (hereinafter also referred to as "HIP") treatment. Patent Document 3 discloses that a zirconia sintered body containing titanium and yttrium in a solid solution, which has a three-point bending strength of 300 MPa or more and is transparent, can be obtained by controlling the degree of reduction of titanium (Ti) in the HIP treatment. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 62-091467 [Patent Document 2] JP 2011-011970 A [Patent Document 3] JP 2011-102227 A Summary of the Invention [Problem to be solved by the invention]
[0005] The sintered bodies disclosed in Patent Documents 2 and 3 have both linear transmittance and high three-point bending strength, which show transparency. Therefore, defects are less likely to occur compared to conventional zirconia sintered bodies in which titanium and yttrium are dissolved, which have transparency. On the other hand, these sintered bodies have low resistance to the development of fractures such as cracks, so that once a defect occurs, the fracture progresses rapidly.
[0006] An object of the present disclosure is to provide a sintered body of zirconia containing titanium and yttrium as a solid solution, which is less prone to fracture than a conventional sintered body of zirconia containing titanium and yttrium as a solid solution and which exhibits transparency, a method for producing the same, and / or uses thereof. [Means for solving the problem]
[0007] In the present disclosure, a titania-yttria-zirconia sintered body having transparency was investigated. As a result, it was found that by controlling the texture of crystal grains, the transparency does not decrease even in a composition that was previously thought to decrease transparency. Furthermore, it was found that a sintered body having such a composition becomes a titania-yttria-zirconia sintered body with improved resistance to the progression of fracture.
[0008] That is, the present invention is as described in the claims, and the gist of the present disclosure is as follows. [1] A sintered body of zirconia in which titanium and yttrium are dissolved, the yttrium content being 3.5 mol% or more and less than 6.0 mol%, and the titanium content being 6.0 mol% or more and 18.5 mol% or less, and the zirconia is composed of cubic crystal grains containing tetragonal domains. [2] The sintered body according to the above [1], which contains alumina. [3] The sintered body according to the above [1] or [2], wherein the crystallite size calculated from the half-width of the peak having a peak top at 2θ=74.0±0.3° in the XRD pattern is 1,400 nm or less. [4] The sintered body according to any one of the above [1] to [3], having an average crystal grain size of 5 μm or more and 50 μm or less. [5] The sintered body according to any one of the above [1] to [4], having an in-line transmittance of 45% or more at a sample thickness of 1±0.1 mm and a measurement wavelength of 600 nm. [6] Fracture toughness value (K IC ) is 1.5MPa m 0.5 The sintered body according to any one of the above [1] to [5]. [7] The sintered body according to any one of [1] to [6] above, having a three-point bending strength of 280 MPa or more. [8] A method for producing a sintered body according to any one of the above [1] to [7], comprising: a primary sintering step of sintering a molded body, which contains a zirconia source, a yttrium source, and a titanium source, and has an yttrium content of 3.5 mol% or more and less than 6.0 mol%, and a titanium content of 6.0 mol% or more and 18.5 mol% or less, in an oxidizing atmosphere at 1260°C or more under normal pressure to obtain a primary sintered body; a pressure sintering step of pressure sintering the primary sintered body in a reducing atmosphere at 1500°C or more to obtain a pressure-treated body; and a heat treatment step of heat-treating the pressure-treated body in an oxidizing atmosphere. [9] The method according to the above item [8], wherein the molded body is obtained by a molding step of molding a raw material powder obtained by a mixing method of mixing a mixed raw material powder of a zirconia source and an yttrium source with a titanium source.
[10] The measured density of the primary sintered body is 5.35 g / cm 3 More than 6.00g / cm 3 The manufacturing method according to the above [8] or [9],
[11] The method according to any one of [8] to
[10] above, wherein the pressure sintering is a hot isostatic pressing process.
[12] The method for producing a semiconductor device according to any one of [8] to
[11] above, wherein the reducing atmosphere is a weakly reducing atmosphere.
[13] The method according to any one of the above [8] to
[12] , wherein the temperature drop rate from the holding temperature to 1000°C in the pressure sintering is 50°C / min or more and 300°C / min or less.
[14] A member comprising the sintered body according to any one of [1] to [7] above. Effect of the Invention
[0009] According to the present disclosure, it is possible to provide a sintered body of zirconia containing titanium and yttrium as a solid solution, which exhibits transparency and is less susceptible to fracture than a conventional sintered body of zirconia containing titanium and yttrium as a solid solution, and which exhibits transparency, a method for producing the same, and / or uses thereof. [Brief description of the drawings]
[0010] [Figure 1] Electron beam diffraction map of the sintered body of Example 1 [Diagram 2] Electron beam diffraction map of the sintered body of Comparative Example 5 [Diagram 3] Rietveld analysis results of the sintered body of Example 1 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The sintered body of the present disclosure will be described below with reference to an example of an embodiment. The configurations and parameters disclosed in this specification can be arbitrarily combined, and the upper and lower limits of the values disclosed in this specification can be arbitrarily combined.
[0012] The "composition" is a substance having a certain composition, and examples thereof include one or more selected from the group consisting of powder, granules, a molded body, a calcined body, and a sintered body.
[0013] The term "powder" refers to a composition that is an aggregate of powder particles and has flowability. The term "zirconia powder" refers to a powder whose main component is zirconia, or a powder that essentially consists of zirconia.
[0014] "Granular powder" refers to a powder consisting of granular particles, and "granular particles" are particles (tertiary particles) formed by the slow aggregation of powder particles (particularly, at least one of primary particles and secondary particles) by physical force, and may contain organic components.
[0015] A "molded body" is a composition having a certain shape composed of powder particles aggregated by physical force, and in particular, a composition in a state in which no heat treatment has been performed after the shape has been imparted (e.g., after molding). A "zirconia molded body" is a molded body whose main component is zirconia, and is a molded body essentially made of zirconia. In this embodiment, the terms "molded body" and "compressed powder" are used interchangeably.
[0016] The term "sintered body" refers to a composition having a certain shape composed of crystal grains, and is a composition in a state in which it has been heat-treated at a temperature equal to or higher than the sintering temperature. The term "zirconia sintered body" refers to a sintered body containing zirconia as a main component, or further, a sintered body essentially consisting of zirconia.
[0017] The term "stabilizing element" refers to an element that has the function of stabilizing the crystal phase of zirconia by dissolving in zirconia.
[0018] The term "powder X-ray diffraction pattern" refers to the XRD pattern of a composition obtained by powder X-ray diffraction (hereinafter also referred to as "XRD") measurement under the following conditions.
[0019] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 1° / min Measurement range: 2θ=20°~80° Acceleration voltage / current: 40kV / 40mA Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm The XRD measurement can be performed using a general X-ray diffractometer (e.g., Ultima IV, manufactured by RIGAKU Corporation). When the composition is a sintered body, the surface of the composition is polished to a surface roughness Ra≦0.02 μm, and the XRD measurement can be performed on the surface.
[0020] Examples of XRD peaks corresponding to each crystal plane of zirconia measured in the above-mentioned XRD measurement include XRD peaks having peak tops at the following 2θ.
[0021] XRD peak corresponding to monoclinic (111) plane: 2θ=31±0.5° XRD peak corresponding to monoclinic (11-1) plane: 2θ=28±0.5° XRD peak corresponding to tetragonal (111) plane: 2θ=30±0.5° XRD peak corresponding to cubic (111) plane: 2θ=30±0.5° XRD peak corresponding to tetragonal (400) plane: 2θ=72.8±0.3° XRD peak corresponding to tetragonal (004) plane: 2θ=74.8±0.3° XRD peak corresponding to cubic (400) plane: 2θ=74.0±0.3° The XRD peak corresponding to the tetragonal (111) plane and the XRD peak corresponding to the cubic (111) plane are measured as a single overlapping peak.
[0022] The XRD peaks can be detected by performing profile fitting of the XRD pattern after smoothing and background removal (hereinafter also referred to as "processed XRD pattern") using a split pseudo-Voigt function. The analysis of the XRD pattern, such as smoothing, background processing, and detection of XRD peaks, can be performed using a program such as an analysis program attached to the X-ray diffraction device (for example, integrated powder X-ray analysis software PDXL Ver. 2.2, manufactured by RIGAKU Corporation) under the following conditions. In this embodiment, what is detected by this is referred to as the XRD peak. The XRD pattern and processed XRD pattern may include minute peaks (so-called noise) that are not detected in the fitting.
[0023] Scherrer constant: 1.000 Smoothing method: β-spline smoothing, γ threshold = 1.50 Background removal method: Straight line connecting endpoints Kα2 ray removal method: intensity ratio=0.497 Peak search method: Peak top method, α cut value = 3.00 Profiling fitting method: Split pseudo-Voigt function [Sintered body] The present embodiment is a zirconia sintered body containing titanium and yttrium, the yttrium content of which is 3.5 mol% or more and less than 6.0 mol%, the titanium content of which is 6.0 mol% or more and 18.5 mol% or less, and which is made of cubic crystal grains including tetragonal domains. This results in a sintered body having the same level of transparency as conventional zirconia sintered bodies made of cubic crystal grains, and higher mechanical strength than these.
[0024] The sintered body of this embodiment is a zirconia sintered body, which is a sintered body having zirconia as the main component (matrix), that is, a so-called zirconia sintered body. Among the zirconia sintered bodies, the sintered body of this embodiment is a zirconia sintered body in which titanium and yttrium are solid-solved, that is, a so-called titania-yttria-zirconia sintered body. In addition, the sintered body of this embodiment is a transparent sintered body, and further a transparent zirconia sintered body, that is, a so-called transparent zirconia sintered body.
[0025] The fact that titanium and yttrium are dissolved in zirconia, and further that the sintered body of this embodiment does not contain titanium and yttrium that are not dissolved in zirconia (undissolved titanium and yttrium) can be determined by the fact that XRD peaks corresponding to titanium compounds and yttrium compounds are not detected in the XRD pattern. Note that it is acceptable to contain undissolved titanium and yttrium to the extent that the effect of the sintered body of this embodiment is not impaired, such as containing undissolved titanium and yttrium to the extent that it is not detected in the XRD pattern. Even in such a case, for convenience, it is considered that the sintered body of this embodiment does not contain undissolved titanium and yttrium.
[0026] Yttrium (Y) dissolves in zirconia and functions as a stabilizing element that stabilizes the zirconia crystal phase. On the other hand, titanium (Ti) dissolves in zirconia, but is not considered to have the function of stabilizing the zirconia crystal phase in the sintered body of this embodiment.
[0027] The sintered body of this embodiment has an yttrium content of 3.5 mol% or more and less than 6.0 mol%. If the yttrium content is less than 3.5 mol%, the sintered body has low transparency, and even if it has translucency, the transparency is extremely low. If the yttrium content is 6.0 mol% or more, the resistance to the progression of fracture is low and the sintered body is easily broken. As a result, it is difficult to apply the sintered body to decorative members and other transparent ceramic applications. In order to obtain a sintered body having fracture toughness and transparency applicable to decorative members and the like, the yttrium content is 4.0 mol% or more, 4.2 mol% or more, 4.35 mol% or more, or 4.5 mol% or more, and may be 5.8 mol% or less, 5.5 mol% or less, less than 5.5 mol%, 5.2 mol% or less, 5.0 mol% or less, or 4.7 mol% or less, and is preferably 4.0 mol% or more and 5.8 mol% or less, 4.0 mol% or more and less than 5.5 mol%, 4.2 mol% or more and 5.5 mol% or less, 4.2 mol% or more and less than 5.5 mol%, 4.2 mol% or more and 5.2 mol% or less, 4.35 mol% or more and 5.2 mol% or less, or 4.5 mol% or more and 5.0 mol% or less.
[0028] The content of yttrium in this embodiment is the ratio [mol %] of the amount of substance [mol] of yttrium converted into Y2O3 to the total amount of substance [mol] of zirconia (ZrO2) and the solid solution element converted into oxide.
[0029] In this embodiment, the solute element is an element that replaces the zirconium (Zr) cation of zirconia, and is contained in the zirconia in the form of a cation. Specific solute elements include at least one selected from the group consisting of titanium (Ti), yttrium (Y), erbium (Er), terbium (Tb), calcium (Ca), magnesium (Mg), lanthanum (La), cerium (Ce), gadolinium (Gd), praseodymium (Pr), Nd (neodymium), samarium (Sm), europium (Eu), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu). The solute elements contained in the sintered body of this embodiment are preferably only yttrium and titanium, and preferably do not contain lanthanum.
[0030] The sintered body of this embodiment preferably does not contain undissolved solid solution elements, but may contain undissolved solid solution elements within a range that does not impair the effects of the sintered body of this embodiment. In this embodiment, the absence of undissolved solid solution elements can be confirmed by detecting no XRD peaks corresponding to the compounds of the solid solution elements in the XRD pattern.
[0031] The sintered body of this embodiment has a titanium content of 6.0 mol% or more and 18.5 mol% or less. If the titanium content is less than 6.0 mol%, crystal grains containing tetragonal crystals are likely to be generated, making it difficult to obtain a sintered body composed of crystal grains made of cubic crystals. If the titanium content exceeds 18.5 mol%, defects will occur during the production (sintering) of the sintered body, and the sintered body will not be obtained. The titanium content is 7.0 mol% or more, 8.0 mol% or more, 9.0 mol% or more, 9.3 mol% or more, 10.0 mol% or more, or 12.0 mol% or more, and can be 17.0 mol% or less, 15.0 mol% or less, or 13.0 mol% or less, and is preferably 7.0 mol% or more and 17.0 mol% or less, 8.0 mol% or more and 15.0 mol% or less, 9.0 mol% or more and 13.0 mol% or less, 9.3 mol% or more and 13.0 mol% or less, or 10.0 mol% or more and 13.0 mol% or less.
[0032] The titanium content in this embodiment is the ratio [mol %] of the amount of substance [mol] of titanium converted into TiO2 to the total amount of substance [mol] of zirconia (ZrO2) and the solid solution element converted into oxide.
[0033] In the sintered body of this embodiment, titanium and yttrium may have the above-mentioned contents, but the total content of titanium and yttrium may be 9.5 mol% or more, 10.0 mol% or more, 13.0 mol% or more, or 15.0 mol% or more, and may be less than 24.5 mol%, 20.0 mol% or less, 18.0 mol% or less, or 17.0 mol% or less, and may be 9.5 mol% or more and less than 24.5 mol%, 10.0 mol% or more and 20.0 mol% or less, 13.0 mol% or more and 20.0 mol% or less, or 15.0 mol% or more and 17.0 mol% or less. The total content of the solute elements in this embodiment may also be a similar amount.
[0034] The sintered body of the present embodiment may be a sintered body made of zirconia in which titanium and yttrium are dissolved, but may also contain alumina (Al2O3) in addition to zirconia in which titanium and yttrium are dissolved. The strength of the sintered body is easily increased by containing alumina.
[0035] The sintered body of this embodiment may not contain alumina (alumina content is 0% by mass), but may contain alumina, and the sintered body of this embodiment may have an alumina content of 0% by mass or more. The alumina content may be 0.15% by mass or less, 0.08% by mass or less, or less than 0.05% by mass. In addition, when alumina is contained, the alumina content may be more than 0% by mass, 0.01% by mass or more, or 0.04% by mass or more. The alumina content of the sintered body of this embodiment may be 0% by mass or more and 0.15% by mass or less, or 0% by mass or more and less than 0.05% by mass, and more preferably more than 0% by mass and 0.15% by mass or less, 0.01% by mass or more and 0.08% by mass or less, or 0.04% by mass or more and 0.08% by mass or less.
[0036] The alumina content in this embodiment may be determined from the ratio [mass %] of the mass of aluminum converted into Al2O3 to the total mass of metal elements in the sintered body converted into oxides (hereinafter also referred to as "metal mass").
[0037] The sintered body of this embodiment is a sintered body of zirconia in which titanium and yttrium are dissolved. Since the sintered body has a zirconia matrix, the composition of the sintered body includes titanium, yttrium, and, if necessary, alumina in addition to zirconia. That is, the composition of the sintered body of this embodiment is essentially zirconia except for yttrium, titanium, and aluminum.
[0038] The sintered body of this embodiment preferably does not contain impurities, but may contain impurities as long as the effect is achieved. Specific impurities include, for example, metal elements and further alkali metal elements. The sintered body of this embodiment may also contain hafnia (HfO2), which is an inevitable impurity of zirconia. In this embodiment, when calculating values related to the composition such as density, hafnia may be regarded as zirconia.
[0039] The composition of the sintered body of this embodiment may be determined as follows, for example, in the case of a sintered body of zirconia containing alumina and in which titanium and yttrium are solid-solved.
[0040] Metal mass [g] =Al2O3+TiO2+Y2O3+ZrO2 Yttrium content [mol%] ={Y2O3 / (ZrO2+Y2O3+TiO2)}×100 Titanium content [mol%] ={TiO2 / (ZrO2+Y2O3+TiO2)}×100 Content of solid solution elements [mol%] ={(Y2O3+TiO2) / (ZrO2+Y2O3+TiO2)}×100 Aluminum content [mass%] ={Al2O3 / (Al2O3+TiO2+Y2O3+ZrO2)}×100 The sintered body of this embodiment is composed of cubic crystal grains, and further composed of cubic crystal grains of zirconia in which yttrium and titanium are dissolved. Cubic crystals are a crystal phase having a shape without anisotropy. Since the sintered body of this embodiment is composed of cubic crystal grains, light scattering due to the anisotropy of the crystal structure does not occur, and the sintered body exhibits high transparency. Note that the sintered body of this embodiment may contain alumina crystal grains in addition to cubic crystal grains (cubic crystal grains of zirconia in which yttrium and titanium are dissolved).
[0041] In this embodiment, for convenience, the crystal phase of zirconia may be considered to consist of three crystal phases, cubic, tetragonal and monoclinic. In addition, the sintered body may be considered to consist of cubic crystal grains if no tetragonal or monoclinic XRD peaks are detected in the XRD pattern of the sintered body. The sintered body of this embodiment may be considered to consist of cubic zirconia, and further, the zirconia contained in the sintered body of this embodiment may be considered to consist of cubic crystal grains. Specifically, the sintered body of this embodiment may be confirmed to consist of cubic crystal grains by having a peak having a peak top at 2θ=74.0±0.3° in the XRD pattern and not having a peak having a peak top at 2θ=72.8±0.3° or not having a peak having a peak top at 2θ=74.8±0.3°.
[0042] In addition, the sintered body of this embodiment is preferably such that the XRD pattern thereof is fitted to a cubic crystal model in a Rietveld analysis using as references an XRD pattern of a zirconia crystal structure model (cubic crystal model) consisting of only cubic crystals and an XRD pattern of a zirconia crystal structure model (mixed crystal model) consisting of a mixed phase of cubic crystals and tetragonal crystals, respectively. This makes it possible to confirm that the sintered body of this embodiment does not contain tetragonal crystal grains and monoclinic crystal grains.
[0043] The Lieveld analysis may be performed using an analysis program (e.g., Rietan-FP), and the cubic crystal model and the mixed crystal model may use a structural model in which the cubic crystal is a cubic crystal having the space group Fm-3m, and the tetragonal crystal is a tetragonal crystal having the space group P42nmc.
[0044] Thus, in the yttrium content of the sintered body of the present embodiment, zirconia is usually a mixed phase consisting of tetragonal crystal grains and cubic crystal grains. In contrast, the sintered body of the present embodiment has the above-mentioned yttrium content and the crystal phase consists only of cubic crystals.
[0045] The sintered body of this embodiment preferably has a moderately high crystallinity of cubic crystals, and the crystallite diameter (hereinafter also simply referred to as "crystallite diameter") calculated from the half-width (hereinafter also referred to as "FWHM") of the peak having a peak top at 2θ=74.0±0.3° in the XRD pattern is preferably 1400nm or less, 1050nm or less, 800nm or less, or 650nm or less. The crystallite diameter can be 150nm or more, 300nm or more, 400nm or more, or 500nm or more, and is preferably 300nm or more to 1400nm or less, 400nm or more to 800nm or less, or 400nm or more to 650nm or less.
[0046] In this embodiment, the crystallite size may be calculated by the following formula.
[0047] D = κλ / βcosθ In the above formula, D is the crystallite size (nm), κ is the Scherrer constant (κ=1.000), λ is the wavelength of the measured X-rays (when CuKα rays are used as the radiation source, λ=0.1548 nm), β is the half-width (°) of the peak having a peak top at 2θ=74.0±0.3°, and θ is the Bragg angle.
[0048] The half-width of the peak having a peak top at 2θ=74.0±0.3° may be determined by fitting the processed XRD pattern obtained by the above-mentioned method.
[0049] The crystal grains constituting the sintered body of this embodiment are cubic crystal grains including tetragonal domains. By including the tetragonal domains, resistance to the progression of fracture is increased, and even if defects such as cracks occur in the sintered body of this embodiment, the expansion of the defects is suppressed. As a result, the fracture toughness value is higher than that of conventional sintered bodies made of cubic crystal grains, and the sintered body is less likely to break.
[0050] The sintered body of this embodiment is mainly composed of zirconia crystal grains (more specifically, zirconia crystal grains in which yttrium and titanium are dissolved). The crystal grains are structures (grains) composed of a plurality of crystallites. In this embodiment, a domain (crystal domain) is a region composed of crystallites having the same crystal structure in a crystal grain. Also, a tetragonal domain is a region composed of crystallites having tetragonal crystals in a cubic crystal grain. Usually, a cubic crystal grain is composed only of crystallites having cubic crystals (only cubic domains). In contrast, the crystal grains constituting the sintered body of this embodiment are cubic crystal grains including tetragonal domains. Therefore, the crystal grains in the sintered body of this embodiment are crystal grains including tetragonal domains in addition to cubic domains, and can also be regarded as crystal grains consisting of cubic domains and tetragonal domains.
[0051] The fact that the sintered body of this embodiment is composed of cubic crystal grains including tetragonal domains can be confirmed by the following method. That is, by detecting the above-mentioned XRD peaks, it can be confirmed that the sintered body is composed of cubic crystal grains. In addition, by obtaining an electron diffraction map of the crystal grains observed in nanodiffraction mapping using a transmission electron microscope (hereinafter also referred to as "TEM") measured under the following conditions, it can be confirmed that the crystal grains include tetragonal domains by observing electron diffraction spots (hereinafter also referred to as "spots") corresponding to the crystal planes of the tetragonal crystals.
[0052] Analysis direction: Tetragonal
[0100] Acceleration voltage: 200Kv Observation magnification: 250,000 times TEM nanodiffraction mapping and electron beam diffraction mapping may be obtained using a general TEM (eg, JEM-F200, manufactured by JEOL Ltd.) and a general electron beam diffraction device (eg, 4D-STEM, manufactured by Gatan).
[0053] Figures 1 and 2 are diffraction patterns of a cubic crystal particle having a tetragonal domain and a cubic crystal particle having no tetragonal domain, respectively. It can be seen that Figure 1 has spots corresponding to tetragonal crystals (the arrows in Figure 1 indicate spots corresponding to the tetragonal (100) plane and its equivalent planes). On the other hand, Figure 2 does not have spots corresponding to tetragonal crystals. As shown in Figure 1, the presence of spots corresponding to tetragonal crystals in the diffraction pattern confirms that the crystal particle contains tetragonal domains.
[0054] The average crystal grain size of the sintered body of this embodiment is 5 μm or more, 10 μm or more, or 15 μm or more, and may be 50 μm or less, 40 μm or less, 30 μm or less, or 20 μm or less. Since the mechanical strength tends to increase as the average crystal grain size becomes smaller, the average crystal grain size of the sintered body of this embodiment is preferably 5 μm to 50 μm, 10 μm to 40 μm, 10 μm to 30 μm, or 15 μm to 30 μm.
[0055] The average crystal grain size is the average diameter of the crystal grains that compose the sintered body, and is a value obtained by the planimetric method from a scanning electron microscope (hereinafter also referred to as "SEM") observation image obtained by observing the surface of the sintered body. Specifically, in order to suppress the variation in the crystal grains observed due to differences in the SEM observation points, two or more SEM observation images, or even two to four SEM observation images, are used, and the number of crystal grains within a circle (n c ) and the number of crystal grains on the circumference (N i ) is 100 ± 30. For all the circles drawn, the crystal grain size of each circle is calculated by the planimetric method, and the average of the results is taken as the average crystal grain size.
[0056] SEM observation for measuring the average crystal grain size may be performed using a general scanning electron microscope (e.g., JSM-IT500LA, manufactured by JEOL Ltd.). SEM observation may be performed by appropriately setting the observation magnification so that the number of crystal grains to be image-analyzed (crystal grains whose grain boundaries are observed without interruption in the SEM image) is 450±50. The conditions for SEM observation may be as follows:
[0057] Acceleration voltage: 15 kV Irradiation current: 40nA Observation magnification: 400x to 10,000x Prior to the measurement, the sintered body samples are surface ground using a #200 grinding wheel, then lapped using diamond abrasives with grain sizes of 3 μm and 1 μm, and then thermally etched in air at a temperature at which the grain boundaries can be confirmed.
[0058] The shape of the sintered body of the present embodiment may be, for example, at least one selected from the group consisting of a sphere, an approximately sphere, an ellipse, a disk, a cylinder, a cube, a rectangular parallelepiped, a polyhedron, and an approximately polyhedron. Furthermore, any shape may be used depending on the purpose of various applications.
[0059] The sintered body of this embodiment has transparency, and for example, the linear transmittance (hereinafter also referred to as "It") at a sample thickness of 1±0.1 mm and a measurement wavelength of 600 nm is 45% or more, or even 50% or more. It is an index showing transparency, and the higher the It, the higher the transparency. Therefore, the It of the sintered body of this embodiment is preferably 52% or more or 55% or more. Although the higher the It, the more preferable, the It of the sintered body of this embodiment can be 75% or less, 70% or less, 65% or less, or 60% or less, and further can be 45% or more and 75% or less, 50% or more and 75% or less, 52% or more and 70% or less, 52% or more and 65% or less, or 55% or more and 60% or less.
[0060] The sintered body of this embodiment preferably has high light transmittance, and for example, the total light transmittance (hereinafter also referred to as "Tt") at a sample thickness of 1±0.1 mm and a measurement wavelength of 600 nm is preferably 60% or more. Tt is one of the indices indicating light transmittance, and the higher the Tt, the higher the light transmittance. The sintered body of this embodiment only needs to satisfy the above-mentioned It, and examples of the Tt include 65% or more, 70% or more, or 71% or more, and 80% or less, 77% or less, 75% or less, or 73% or less. Examples of the Tt of the sintered body of this embodiment include 60% or more and 80% or less, 65% or more and 80% or less, 70% or more and 75% or less, and 71% or more and 75% or less.
[0061] In order to make it easier to obtain a transparent member with higher aesthetic appeal, it is preferable that the ratio of It to Tt (hereinafter also referred to as "It / Tt ratio") is high, and the It / Tt ratio of the sintered body of this embodiment is 0.95 or less, 0.90 or less, or 0.85 or less. In order to obtain a highly aesthetic transparency, It / Tt is 0.70 or more or 0.75 or less, and is 0.70 or more and 0.95 or less, 0.70 or more and 0.90 or less, or 0.75 or more and 0.85 or less.
[0062] In this embodiment, Tt and It are both light transmittances obtained by measuring according to JIS K 7361-1. The ratio of transmitted light (total of linear transmitted light and diffuse transmitted light) to incident light is the total light transmittance [%], and the ratio of linear transmitted light to incident light is the linear transmittance [%], and the relationship is total light transmittance [%] = linear transmittance [%] + diffuse transmittance [%]. The measurement sample is a disk-shaped sintered body having a sample thickness of 1.0 ± 0.1 mm and a surface roughness Ra ≦ 0.02 μm on both sides, and the measurement device is a general spectrophotometer (for example, a spectrophotometer V-650 manufactured by JASCO Corporation).
[0063] The sintered body of the present embodiment has high transparency and high resistance to the progression of fracture. The sintered body of the present embodiment has a fracture toughness value (K IC ) is 1.5MPa m0.5 More than 2.0MPa m 0.5 or more than 2.2MPa m 0.5 It is preferable that the fracture toughness value is high, and the fracture toughness value of the sintered body of this embodiment is 3.0 MPa m 0.5 Below, 2.8MPa m 0.5 Less than or equal to 2.6MPa m 0.5 For example, the following can be used: 1.5 MPa m 0.5 More than 3.0MPa m 0.5 Below, 2.0MPa m 0.5 More than 3.0MPa m 0.5 Less than or equal to 2.2MPa m 0.5 More than 2.8MPa m 0.5 It is preferable that:
[0064] In this embodiment, the "fracture toughness value (K IC ) is the fracture toughness value [MPa m 0.5 The fracture toughness value is measured using a columnar sintered body sample with a support distance of 30 mm, width of 4 mm, and thickness of 3 mm, and the average value of 10 measurements may be used as the fracture toughness value of the sintered body of this embodiment. In addition, a general strength tester (for example, Instron Tester Model 5582, manufactured by Instron) may be used for the measurement. In addition, JIS R 1607 specifies two methods of fracture toughness measurement, the IF method and the SEPB method. The IF method tends to measure larger values than the SEPB method. Furthermore, since the IF method is a simple measurement method, the measured values vary greatly from measurement to measurement. Therefore, the absolute values of the fracture toughness value in this embodiment and the fracture toughness value measured by the IF method cannot be compared. Similarly, the absolute values of the fracture toughness value measured by a method other than the SEPB method and the fracture toughness value measured by the SEPB method cannot be compared.
[0065] The sintered body of this embodiment preferably has high strength so that it is less likely to break when processed, and the three-point bending strength of the sintered body of this embodiment is preferably 280 MPa or more, 310 MPa or more, 350 MPa or more, or 420 MPa or more. The strength of the sintered body of this embodiment may be sufficient as long as it is suitable for processing, and examples of the three-point bending strength include 800 MPa or less, 750 MPa or less, 700 MPa or less, or 600 MPa or less, and examples thereof include 280 MPa or more and 800 MPa or less, 310 MPa or more and 700 MPa or less, or 420 MPa or more and 600 MPa or less.
[0066] The "three-point bending strength" in this embodiment is a value measured by a method conforming to JIS R 1601. The measurement sample is a columnar shape with a width of 4 mm, a thickness of 3 mm, and a length of 45 mm, with a support distance of 30 mm, and a load is applied in the horizontal direction of the measurement sample. A general strength testing machine (for example, a desktop universal precision testing machine AGX-10kNX, manufactured by Shimadzu Corporation) may be used for the measurement.
[0067] The sintered body of this embodiment may be a sintered body (hereinafter, also referred to as a "compound sintered body") consisting of the sintered body of this embodiment and a sintered body other than the sintered body of this embodiment. The compound sintered body is a sintered body in which the sintered body of this embodiment and a sintered body other than the sintered body of this embodiment are integrated by sintering, and this results in a more aesthetically pleasing member. Here, the "integrated state by sintering" is different from a state in which the sintered body is integrated by the use of an adhesive, a physical structure such as interlocking, or other physical action, and means that the sintered body of this embodiment and the sintered body other than the sintered body of this embodiment are integrated by forming an interface.
[0068] The sintered body other than the sintered body of this embodiment contained in the compound sintered body may be a sintered body having different aesthetics from the sintered body of this embodiment, but is preferably a zirconia sintered body, and more preferably an opaque zirconia sintered body. An example of the opaque zirconia sintered body is a zirconia sintered body having an It of 0% or more and 5% or less, further 0% or more and 3% or less, further 0% or more and 1% or less, particularly 0% or more and 0.5% or less. An example of the sintered body other than the sintered body of this embodiment contained in the compound sintered body is a zirconia sintered body exhibiting a chromatic color or an achromatic color, and an example of the zirconia sintered body exhibiting an achromatic color is a white, gray, or black zirconia sintered body. On the other hand, an example of the chromatic zirconia sintered body is a zirconia sintered body exhibiting a red, orange, yellow, green, blue, indigo, or purple color, and even a zirconia sintered body exhibiting a black color.
[0069] The sintered body of the present embodiment can be used as a transparent ceramic, for example, as one or more selected from the group consisting of optical members, exterior members, and decorative members. The sintered body of the present embodiment may also be used as a member including these. [Method of manufacturing sintered body] The method for producing the sintered body of this embodiment may be any method as long as it can produce a sintered body that satisfies the above-mentioned configuration. A preferred method for producing a sintered body includes a primary sintering step in which a molded body containing a zirconia source, an yttrium source, and a titanium source, and having an yttrium content of 3.5 mol% or more and less than 6.0 mol%, and a titanium content of 6.0 mol% or more and 18.5 mol% or less is sintered under atmospheric pressure at 1260°C or more in an oxidizing atmosphere to obtain a primary sintered body, a pressure sintering step in which the primary sintered body is pressure sintered at 1500°C or more in a reducing atmosphere to obtain a pressure-treated body, and a heat treatment step in which the pressure-treated body is heat-treated in an oxidizing atmosphere (hereinafter, also referred to as the "production method of this embodiment"). The production method of this embodiment can produce a zirconia sintered body consisting of a crystal phase consisting of only cubic crystals, despite the composition that was previously thought to produce only a zirconia sintered body consisting of a mixed phase of tetragonal and cubic crystals.
[0070] The manufacturing method of this embodiment includes a primary sintering step of obtaining a primary sintered body by atmospheric pressure sintering a molded body containing a zirconia source, an yttrium source, and a titanium source, and having an yttrium content of 3.5 mol% or more and less than 6.0 mol% and a titanium content of 6.0 mol% or more and 18.5 mol% or less. This produces a primary sintered body to be subjected to pressure sintering treatment.
[0071] In the primary sintering step, a molded body having an yttrium content of 3.5 mol % or more and less than 6.0 mol % and a titanium content of 6.0 mol % or more and 18.5 mol % or less, and containing a zirconia source, an yttrium source, and a titanium source is provided.
[0072] The zirconia source may be zirconia (ZrO2).
[0073] The yttrium source may be any yttrium compound, and may be one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, and halides containing yttrium. At least one of yttrium chloride and oxide, and further at least one of yttrium oxide (yttria; Y2O3) and yttrium chloride (YCl3) are preferred, with yttrium oxide being more preferred.
[0074] The molded body may contain yttrium-doped zirconia (yttrium-stabilized zirconia) in addition to zirconia and yttrium compound or instead of zirconia and yttrium compound. Furthermore, it is preferable that the molded body contains yttrium-doped zirconia instead of zirconia and yttrium compound (i.e., the zirconia source and the yttria source are yttrium-doped zirconia). The yttrium-doped zirconia is zirconia stabilized by dissolving yttrium in a solid solution, that is, so-called yttrium-stabilized zirconia.
[0075] The titanium source may be any titanium compound, and may be one or more selected from the group consisting of oxides, hydroxides, oxyhydroxides, and halides containing titanium. The titanium source may be at least one of chlorides and oxides containing titanium, and may further be at least one of titanium oxide (titania; TiO2) and titanium chloride (TiCl4), or may further be titanium oxide.
[0076] The molded body may contain an alumina source. The alumina source may be at least one of alumina and a precursor thereof, and is preferably alumina (Al2O3).
[0077] The molded body may contain a binder. By containing a binder, the operability (handling) and shape retention are improved. The binder may be any binder that can be used for granulating and molding ceramics, and is preferably an organic binder. The organic binder is at least one selected from the group consisting of polyvinyl alcohol, polyvinyl butyrate, wax, and acrylic resin, preferably at least one of polyvinyl alcohol and acrylic resin, and more preferably acrylic resin. In this embodiment, the acrylic resin is a polymer containing at least one of acrylic acid ester and methacrylic acid ester. Specific examples of the binder include at least one selected from the group consisting of AS-1100, AS-1800, and AS-2000 (all product names, manufactured by Toa Gosei Co., Ltd.).
[0078] The composition of the molded body is such that the yttrium content is 3.5 mol% or more and less than 6.0 mol%, and the titanium content is 6.0 mol% or more and 18.5 mol% or less, and further, it is sufficient that the molded body contains metal elements in a composition similar to that of the target sintered body, and further, it is sufficient that the molded body contains metal elements in a composition similar to that of the above-mentioned sintered body.
[0079] When a binder is contained, the content of the binder is, for example, 0.5% by mass or more, or 1% by mass or more, and 10% by mass or less, or 5% by mass or less. The content of the binder may be calculated as follows.
[0080] {(W2-W1) / W2} x 100 In the above formula, W1 is the mass [g] of the molded body after heat treatment in the air at 250°C to 400°C, and W2 is the mass [g] of the molded body before the heat treatment. Note that due to differences in calculation methods, the composition of the molded body including the binder does not necessarily have to be 100% by mass.
[0081] The molded body may be produced by any method as long as the zirconia source, the yttrium source, the titanium source, and, if necessary, the alumina source are uniformly contained in the molded body. For example, the molded body may be produced by a method including a molding step of molding a powder containing the zirconia source, the yttrium source, and the titanium source.
[0082] In the molding step, powders similar to the above-mentioned zirconia source, yttrium source, and titanium source (hereinafter, each will be referred to as "starting raw materials" and collectively referred to as "raw material powders") may be provided. The raw material powders may contain an alumina source. Furthermore, the manufacturing method of this embodiment has a pressure sintering step. Since pressure sintering is less affected by the sinterability of the starting raw materials, the starting raw materials may be commercially available powders (e.g., reagent grade powders) or granular powders.
[0083] The starting materials (zirconia source, yttrium source, titanium source and alumina source) are preferably powders having similar particle sizes, and each has an average particle size of, for example, 0.2 μm or more or 0.4 μm or more and 0.6 μm or less or 0.5 μm or less, and preferably 0.4 μm or more and 0.6 μm or less, or 0.4 μm or more and 0.5 μm or less.
[0084] The average particle size of the raw material powder may be the same as that of the starting raw material, and is preferably 0.4 μm to 0.6 μm, or 0.4 μm to 0.5 μm. Furthermore, in order to obtain a primary sintered body in which tetragonal domains are likely to be generated in the pressure sintering under the conditions described below, the ratio of the standard deviation [μm] of the particle size to the average particle size [μm] of the raw material powder (hereinafter also referred to as the "particle size standard deviation") is preferably 0.5 or less or 0.3 or less. Since a practical powder has a distribution of particle sizes, the particle size standard deviation of the raw material powder may be more than 0 or 0.01 or more, and is preferably more than 0 and 0.5 or less, more than 0 and 0.3 or less, or 0.01 or more and 0.3 or less.
[0085] The raw material powders may be mixed by at least one of a dry method and a wet method so that the starting materials are uniform, and wet mixing is preferable. Specifically, for example, mixing may be performed by at least one of agitation mixing, a ball mill, and a bead mill.
[0086] A preferred method for mixing the starting materials includes a method of mixing a mixed raw material powder of a zirconia source and an yttrium source with a titanium source. The mixed raw material powder may include an alumina source. The raw material powder is a precursor of a molded body containing a zirconia source as a main component, an yttrium source, a titanium source, and an alumina source. By mixing the titanium source with zirconia in a state in which the yttrium source and the alumina source have been incorporated, it is believed that titanium is easily dissolved in zirconia in a state in which a tetragonal domain is easily generated in the subsequent primary sintering and pressure sintering. In addition, a more preferred mixing method includes a mixing method of mixing a slurry containing a mixed raw material powder of a zirconia source and an yttrium source with a slurry containing a titanium source. By mixing slurries with controlled pulverized particle size, it is believed that the physical properties of the obtained raw material powder are more easily controlled, and the tetragonal domain of the sintered body obtained by the subsequent primary sintering and pressure sintering is more easily generated stably.
[0087] The molding method may be any known molding method for ceramic molded bodies (compressed powder bodies) and may be any molding method suitable for the shape of the desired molded body. The molding method may be one or more selected from the group consisting of uniaxial pressing, injection molding, slip casting, sheet molding, and cold isostatic pressing (hereinafter also referred to as "CIP") treatment, and is preferably one or more selected from the group consisting of uniaxial pressing, injection molding, and CIP treatment, and more preferably primary pressing and CIP treatment.
[0088] The molded body to be subjected to the primary sintering step is preferably a molded body obtained by a molding step of molding a raw material powder obtained by a mixing method of mixing a mixed raw material powder of a zirconia source and a yttrium source with a titanium source, and more preferably a molded body obtained by a molding step of molding a raw material powder obtained by a mixing method of mixing a slurry containing a mixed raw material powder of a zirconia source and a yttrium source with a slurry containing a titanium source.
[0089] In the primary sintering step, the above-mentioned molded body is sintered under atmospheric pressure at 1260°C or higher in an oxidizing atmosphere to obtain a primary sintered body. In the composition of the molded body to be subjected to the primary sintering step, the primary sintered body is obtained as a sintered body in a state in which there are no open pores by such primary sintering. In this embodiment, atmospheric sintering is a method of sintering by heating without applying an external force to the sintered object (such as a molded body or a calcined body) during sintering. In the composition of the molded body to be subjected to the primary sintering step, if the primary sintering is performed at less than 1260°C, the sintered body obtained after pressure sintering has extremely low transparency or no transparency. The holding temperature of the primary sintering (hereinafter also referred to as the "primary sintering temperature") is preferably 1300°C or higher or 1325°C or higher. The upper limit of the primary sintering temperature can be, for example, 1500°C or lower or 1400°C or lower. The following conditions can be given as preferable conditions for atmospheric sintering.
[0090] Sintering atmosphere: Oxidizing atmosphere, preferably air atmosphere Primary sintering temperature: 1260°C or higher, 1300°C or higher, or 1325°C or higher; and 1500℃ or less or 1400℃ or less Heating rate: 50°C / hour or more or 80°C / hour or more, and 200℃ / hour or less or 120℃ / hour or less The holding time at the holding temperature may be appropriately adjusted depending on the size of the molded body to be subjected to the primary sintering step and the performance of the primary sintering furnace, and may be, for example, from 30 minutes to 15 hours, or from 1 hour to 1.5 hours.
[0091] The primary sintered body obtained in the primary sintering process must contain only closed pores. The phase density in this embodiment differs depending on the composition, but the relative density of the primary sintered body is preferably 90% or more and 98% or less. This is because the measured density in the composition range of the sintered body in this embodiment is 5.35 g / cm 3 More than 5.40g / cm 3 More than 5.60g / cm 3 or more than 5.80g / cm 3 More than 6.00 g / cm 3 Below, 5.90g / cm 3 Less than or equal to 5.85g / cm 3 The following are listed as being below: 5.35 g / cm 3 More than 6.00g / cm 3 Below, 5.40g / cm 3 More than 5.9g / cm 3 Below, 5.60g / cm 3 More than 5.85g / cm 3 Below, 5.80g / cm 3 More than 5.85g / cm 3 The following is preferred:
[0092] In this embodiment, the "measured density" is the density of the sample volume [cm 3 ] and the value [g / cm 3 The mass is determined by weighing the sample, and the volume is determined by the Archimedes method according to JIS R 1634. The Archimedes method uses ion-exchanged water as the solvent, and the pretreatment is performed by boiling.
[0093] The average crystal grain size of the primary sintered body may be any size that allows pores to be easily removed during pressure sintering, and is preferably 1.0 μm or less, and more preferably 0.8 μm or less. The average crystal grain size of the primary sintered body may be 0.1 μm or more or 0.3 μm or more, and may be 0.1 μm or more to 1.0 μm or less, or 0.3 μm or more to 0.8 μm or less.
[0094] The manufacturing method of this embodiment includes a pressure sintering step in which the primary sintered body is pressure sintered in a reducing atmosphere to obtain a pressure-treated body. The pressure sintering removes closed pores contained in the primary sintered body by mass transfer. As a result, the primary sintered body is densified to such an extent that the sintered body after heat treatment exhibits high transparency. When the primary sintered body is sintered in a reducing atmosphere without pressure, a sintered body having translucency may be obtained, but such a sintered body has no transparency or has extremely low transparency.
[0095] Pressure sintering is carried out in a reducing atmosphere. By pressure sintering in a reducing atmosphere, the titanium contained in the primary sintered body is reduced to trivalent titanium (Ti 3+ ) and the formation of oxygen vacancies. The formation of oxygen vacancies promotes mass transfer, which effectively eliminates closed pores and results in a dense sintered body. Furthermore, a sintered body with high transparency can be obtained by the subsequent heat treatment step. Even if the primary sintered body is sintered under atmospheric pressure, the resulting sintered body may have translucency in some cases, but a sintered body that has both high translucency and high transparency cannot be obtained.
[0096] Since a mass transfer suitable for efficient elimination of closed pores is likely to occur, the reducing atmosphere is preferably a weakly reducing atmosphere, and more preferably an inert atmosphere in which a reducing member coexists. The inert gas atmosphere may be an argon atmosphere or a nitrogen atmosphere, and an argon atmosphere is preferred. The reducing member may be a member made of a reducing material, and a carbon member is preferred.
[0097] In the pressure sintering, the primary sintered body is placed in a container and pressure sintered. At least one of the members constituting the pressure sintering furnace (hereinafter also referred to as "furnace members") and the container in which the primary sintered body is placed (hereinafter also referred to as "sintering container") may be a reducing member, and at least one of the furnace members and the sintering container may be a carbon member, and it is preferable that the furnace members and the sintering container are carbon members.
[0098] A preferred weakly reducing atmosphere is an argon atmosphere or a nitrogen atmosphere in which one or more selected from the group consisting of a heating element, a heat insulating material, and a sintering vessel are carbon components, and a more preferred weakly reducing atmosphere is an argon atmosphere in which the heating element and the sintering vessel are carbon components.
[0099] The pressure sintering may be at least one of a hot press treatment and a hot isostatic press treatment (HIP treatment), with the HIP treatment being preferred.
[0100] The holding temperature in the pressure sintering (hereinafter also referred to as "pressure sintering temperature") may be any temperature at which elimination of closed pores can be promoted by mass transfer, and is 1500°C or higher, preferably 1525°C or higher or 1550°C or higher. If the pressure sintering temperature is less than 1500°C, the mechanical strength may be high, but the sintered body may have significantly low transparency. As the pressure sintering temperature increases, the transparency tends to increase. Since a general-purpose HIP processing device can be used, the holding temperature may be 1700°C or lower, 1650°C or lower, or 1645°C or lower.
[0101] In order to obtain a sintered body having a higher fracture toughness value, the pressure sintering temperature is preferably 1600°C or less, more preferably less than 1600°C, and even more preferably 1575°C or less. If the pressure sintering temperature is within the above-mentioned range, a sintered body having both linear transmittance and fracture toughness value can be obtained. On the other hand, if the pressure sintering temperature is appropriately low within the above-mentioned range, a sintered body having both linear transmittance and fracture toughness value and having a higher fracture toughness value can be obtained, so the pressure sintering temperature is preferably 1500°C or more and 1645°C or less, more preferably 1500°C or more and 1600°C or less, and even more preferably 1525°C or more and 1575°C or less.
[0102] The pressure in the pressurization treatment may be any pressure that can promote the elimination of closed pores by the pressurization treatment, and may be 50 MPa or more or 100 MPa or more, and may be 200 MPa or less or 170 MPa or less, such as 50 MPa or more and 200 MPa or less, or 100 MPa or more and 170 MPa or less.
[0103] The treatment time at the pressure sintering temperature may be appropriately adjusted depending on the size of the primary sintered body and the characteristics of the pressure sintering furnace, and may be, for example, from 10 minutes to 10 hours, or from 30 minutes to 5 hours.
[0104] In the pressure sintering, the temperature may be increased to the pressure sintering temperature at a rate of 5° C. / min or more or 10° C. / min or more. Although there is no upper limit to the rate of temperature increase, since a general-purpose pressure sintering furnace can be used, the rate of temperature increase can be, for example, 100° C. / min or less or 50° C. / min or less.
[0105] Since tetragonal domains are easily generated in cubic crystal grains, the cooling rate from the pressure sintering temperature to 1000°C is preferably 50°C / min or more or 70°C / min or more. The upper limit of the cooling rate may be appropriately set depending on the pressure sintering furnace used, and may be 300°C / min or less or 150°C / min or less. In this embodiment, the cooling rate from the pressure sintering temperature to 1000°C may be 50°C / min or more and 300°C / min or less, 70°C / min or more and 150°C / min or less, or 70°C / min or more and 100°C / min or less.
[0106] The manufacturing method of this embodiment includes a heat treatment step of heat treating the treated body in an oxidizing atmosphere. 3+ ) is oxidized to tetravalent titanium (Ti 4+ ) oxygen defects are eliminated, and the sintered body of this embodiment having transparency can be obtained.
[0107] The oxidizing atmosphere may be an oxygen atmosphere or an air atmosphere, with the air atmosphere being preferred.
[0108] The holding temperature in the heat treatment (hereinafter also referred to as "heat treatment temperature") should be 800°C or more or 850°C or more at which the oxidation of titanium proceeds efficiently, and may be less than 1200°C or less than 1100°C, with 800°C or more and less than 1200°C, or 850°C or more and 1100°C or less being preferred.
[0109] The holding time at the heat treatment temperature may be adjusted appropriately depending on the size of the body to be treated and the performance of the heat treatment furnace, but may be, for example, from 30 minutes to 10 hours, or from 45 minutes to 3 hours. EXAMPLES
[0110] The present disclosure will be described in detail below with reference to examples. However, the present disclosure is not limited to these examples.
[0111] (composition analysis) The composition of the composition was determined by ICP analysis.
[0112] (XRD measurement) An XRD pattern of the sintered body was obtained by XRD measurement using an X-ray diffractometer (for example, Ultima IV, manufactured by RIGAKU Corporation) under the following conditions.
[0113] Radiation source: CuKα radiation (λ=0.15418nm) Measurement mode: Continuous scan Scan speed: 1° / min Measurement range: 2θ=20°~80° Acceleration voltage / current: 40mA / 40kV Divergence vertical limit slit: 10mm Divergence / entrance slit: 1° Receiving slit: open Detector: Semiconductor detector (D / teX Ultra) Filter: Ni filter Goniometer radius: 185mm Prior to the measurement, the surface of the sintered body was polished to a surface roughness Ra≦0.02 μm to prepare a measurement sample, and the surface was subjected to XRD measurement.
[0114] Using an analysis program (product name: Integrated Powder X-ray Analysis Software PDXL Ver.2.2, manufactured by RIGAKU), smoothing and background removal were performed, and the XRD pattern (processed XRD pattern) was analyzed by profile fitting using a divided pseudo-Voigt function. The smoothing, background removal, and analysis conditions are shown below.
[0115] Scherrer constant: 1.000 Smoothing method: β-spline smoothing, γ threshold = 1.50 Background removal method: Straight line connecting endpoints Kα2 ray removal method: intensity ratio=0.497 Peak search method: Peak top method, α cut value = 3.00 Profiling fitting method: Split pseudo-Voigt function Prior to the measurement, the surface of the sintered body was polished with sandpaper having a grain size of #400 in accordance with JIS R 6001-2, and then lapped and polished with a diamond abrasive having a grain size of 3 μm.
[0116] For the obtained XRD patterns, a Rietveld analysis was performed using an analysis program (Rietan-FP) with a cubic crystal model and a mixed crystal model with a cubic crystal having a space group of Fm-3m as a cubic crystal and a tetragonal crystal having a space group of P42nmc as a tetragonal crystal.
[0117] (Crystallite diameter) The crystallite size in this embodiment was calculated by the following formula.
[0118] D = κλ / βcosθ In the above formula, D is the crystallite size (nm), κ is the Scherrer constant (κ=1.000), λ is the wavelength of the measured X-rays (when CuKα rays are used as the radiation source, λ=0.1548 nm), β is the half-width (°) of the peak having a peak top at 2θ=74.0±0.3°, and θ is the Bragg angle.
[0119] The half-width of the peak having a peak top at 2θ=74.0±0.3° was determined by analysis under the same conditions as those for the above-mentioned XRD measurement.
[0120] (Actual density) The measured density is the mass of the sample [cm 3 The mass was calculated from the mass [g] relative to the volume of the sample. The mass was determined by weighing the sample, and the volume was determined by the Archimedes method according to JIS R 1634. The Archimedes method used ion-exchanged water as the solvent, and pretreatment was performed by boiling.
[0121] (TEM Nanodiffraction) Using a field emission type transmission electron microscope (instrument name: JEM-F200, manufactured by JEOL Ltd.) and an electron beam diffraction device (instrument name: 4D-STEM, manufactured by Gatan), TEM nanodiffraction mapping and diffraction patterns were obtained by analyzing the crystal particles observed by TEM nanodiffraction mapping from the tetragonal
[0100] orientation, and tetragonal spots were confirmed.
[0122] Acceleration voltage: 200Kv Observation magnification: 250,000 times (Total light transmittance and in-line transmittance) Tt and It were measured under the following conditions using a general UV-VIS spectrophotometer (instrument name: Spectrophotometer V-650, manufactured by JASCO Corporation). In the obtained spectrum, the total light transmittance and linear transmittance at a wavelength of 600 nm were defined as Tt and It, respectively. The measurement sample used was a disk-shaped sintered body with a thickness of 1±0.1 mm and a surface roughness on both sides of Ra≦0.02 μm.
[0123] Measurement method: UV-VIS spectrophotometry Measurement method: Double beam method Light source:D2 / WI Measurement wavelength range: 200nm~900nm Data capture interval: 0.5 nm (Three-point bending strength) The three-point bending strength was measured according to the method of JIS R 1601. The measurement sample was a column shape with a width of 4 mm, a thickness of 3 mm, and a length of 45 mm, with a support distance of 30 mm, and a load was applied horizontally to the measurement sample. A strength testing machine (device name: desktop universal precision testing machine AGX-10kNX, manufactured by Shimadzu Corporation) was used for the measurement.
[0124] (Fracture toughness value) The fracture toughness value (K IC ) [MPa m 0.5 The fracture toughness of the sintered body of this embodiment was determined by averaging the results of 10 measurements. A strength tester (e.g., Instron Tester Model 5582, manufactured by Instron Corporation) was used for the measurement.
[0125] (Average grain size) The average crystal grain size was determined from SEM observation images taken under the following conditions using a scanning electron microscope (device name: JSM-IT500LA, manufactured by JEOL Ltd.).
[0126] Acceleration voltage: 15 kV Irradiation current: 40nA Observation magnification: 400x to 10,000x Prior to the measurement, the sintered samples were surface ground using a #200 grindstone, lapped using diamond abrasives with grain sizes of 3 μm and 1 μm, and then thermally etched in air for 1 hour. The thermal etching temperature was 100°C lower than the sintering temperature.
[0127] Three SEM images were used, and the number of crystal grains within a circle (n c ) and the number of crystal grains on the circumference (N i ) was drawn to give a total of 100±30. The crystal grain size of each of the drawn circles was calculated by the planimetric method, and the average value was taken as the average crystal grain size.
[0128] Example 1 A powder of yttrium-stabilized zirconia containing alumina with an yttrium content of 5.5 mol% and an aluminum content of 0.05 mass% was mixed with pure water. After mixing, the mixture was wet-pulverized in a ball mill until the average particle size was 0.5 μm and the standard deviation of the particle size was 0.1 μm, to obtain a zirconia slurry with a powder content (solid content concentration) of 45 mass%. The standard deviation of the particle size of the obtained powder was 0.2.
[0129] On the other hand, titania powder was mixed with pure water and wet-pulverized in a ball mill until the average particle size was 0.5 μm and the standard deviation of the particle size was 0.1 μm, to obtain a titania slurry with a powder content (solid content concentration) of 20 mass %. The standard deviation of the particle size of the obtained powder was 0.2.
[0130] The obtained zirconia slurry and titania slurry were mixed so that the mass ratio of the zirconia powder to the titania powder was 92:8, and a mixed slurry containing yttrium-stabilized zirconia powder containing alumina and titania was obtained, with the yttrium content being 4.67 mol%, the aluminum content being 0.046 mass%, and the titania content being 8 mass% (12.29 mol%).
[0131] The resulting mixed slurry was spray-dried at 180° C. to obtain a granular powder of yttrium-stabilized zirconia containing alumina and titania, with an yttrium content of 4.67 mol %, an aluminum content of 0.046 mass %, and a titania content of 8 mass %.
[0132] The obtained granular powder (3 g) was filled into a mold having an inner diameter of 25 mm, and then uniaxial press molding was performed at a pressure of 98 MPa. After molding, CIP processing was performed at a pressure of 196 MPa to obtain a disk-shaped molded body having a diameter of 25 mm.
[0133] The obtained molded body was subjected to primary sintering under the following conditions to obtain a primary sintered body made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%. The primary sintered body had an average crystal grain size of 0.6 μm and a measured density of 5.82 g / cm. 3 It was.
[0134] Primary sintering atmosphere: Air Heating rate: 100℃ / hour Holding temperature: 1350℃ Holding time: 2 hours The obtained primary sintered body was placed in a carbon container with a lid, and the carbon container was placed in a HIP device equipped with a carbon heating element, and then HIP-treated in a weakly reducing atmosphere under the following conditions to obtain a HIP-treated body.
[0135] Pressure medium: Argon gas (purity: 99.9%) Heating rate: 10℃ / min Holding temperature: 1550℃ Holding pressure: 150MPa Holding time: 1 hour After that, the temperature was lowered to 1000°C at a rate of 80°C / min.
[0136] The obtained HIP-treated body was heat-treated in an air atmosphere at 900°C for 1 hour to obtain a sintered body of this example made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%.
[0137] FIG. 1 shows the TEM diffraction mapping results of the sintered body of this embodiment. In FIG. 1, the spots of the tetragonal (100) plane and the crystal plane of the tetragonal crystal equivalent thereto were confirmed (enclosed part in FIG. 1), and it was confirmed that all of them were tetragonal spots of 5 nm or less. In addition, in the Rietveld analysis result of the XRD pattern of the sintered body of this embodiment shown in FIG. 3, it was confirmed that the sintered body of this embodiment is 100% cubic. From this, it was confirmed that the sintered body of this embodiment is a sintered body composed of cubic crystal grains having a tetragonal domain. The sintered body of this embodiment had an average crystal grain size of 18 μm and a crystallite size of 448 nm.
[0138] Example 2 A sintered body of this example was obtained by the same method as in Example 1, except that the primary sintering temperature was 1300° C. The sintered body was made of alumina-containing titania and yttrium-doped zirconia, with the yttrium content being 4.67 mol%, the titanium content being 12.29 mol%, and the alumina content being 0.046 mass%. The measured density of the obtained primary sintered body was 5.40 g / cm. 3 The sintered body of this example had a crystallite diameter of 934 nm.
[0139] Example 3 A sintered body of this example was obtained by the same method as in Example 1, except that the holding temperature in the HIP treatment was 1500°C. The sintered body was made of alumina-containing titania and yttrium-doped zirconia, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%. The measured density of the obtained primary sintered body was 5.82 g / cm. 3 The sintered body of this example had a crystallite diameter of 804 nm.
[0140] Example 4 A sintered body of this example was obtained by the same method as in Example 1, except that the holding temperature in the HIP treatment was 1600°C. The sintered body was made of alumina-containing titania and yttrium-doped zirconia, with the yttrium content being 4.67 mol%, the titanium content being 12.29 mol%, and the alumina content being 0.046 mass%. The measured density of the obtained primary sintered body was 5.82 g / cm. 3 The average crystal grain size of the sintered body of this example was 36.0 μm, and the crystallite diameter was 678 nm.
[0141] Comparative Example 1 A sintered body of this comparative example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%, by the same method as in Example 1, except that the primary sintered body was treated by normal pressure sintering in an air atmosphere at a heating rate of 600°C / hour, a holding temperature of 1550°C, and a holding time of 1 hour, instead of the HIP treatment.
[0142] The sintered body of this comparative example was a sintered body composed of cubic crystal grains and tetragonal crystal grains, and had low light transmittance and no transparency.
[0143] Comparative Example 2 A sintered body of this comparative example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%, in the same manner as in Example 1, except that the primary sintering temperature was set to 1250° C. The sintered body of this comparative example had a low Tt and was not transparent, although it had translucency.
[0144] Comparative Example 3 The sintered body of this comparative example was obtained in the same manner as in Example 1, except that the primary sintered body was subjected to atmospheric sintering (reducing atmospheric sintering) in a 95% argon-5% hydrogen mixed gas atmosphere as the reducing atmosphere, the holding temperature was 1550°C, and the holding time was 1 hour, and that the HIP treatment was not performed. Although the sintered body of this comparative example was obtained by sintering in a reducing atmosphere, it had low light transmittance and did not have transparency.
[0145] Comparative Example 4 A sintered body of this comparative example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.67 mol%, titanium content of 12.29 mol%, and alumina content of 0.046 mass%, in the same manner as in Example 1, except that the treatment temperature in the HIP treatment was 1450° C. The sintered body of this comparative example had low translucency and was not transparent.
[0146] Comparative Example 5 A sintered body of yttrium- and titania-stabilized zirconia with an yttrium content of 9.0 mol% and a titanium content of 10 mol% was obtained by the same method as in Example 3 of JP 2011-102227 A. That is, commercially available zirconia powder (product name: TZ-10Y, manufactured by Tosoh Corporation) and titania powder (product name: PT-401M, manufactured by Ishihara Sangyo Kaisha) were weighed so that the yttrium content was 9.0 mol% and the titania content was 10 mol%, and mixed in a ball mill for 72 hours using zirconia balls with a diameter of 10 mm as a grinding medium, and dried powder was prepared to be used as the raw material powder.
[0147] The raw material powder was molded using a die press at a pressure of 50 MPa, and then further consolidated at a pressure of 200 MPa using a cold isostatic press to obtain a cylindrical compact with a diameter of 20 mm.
[0148] The green body was subjected to primary sintering in an air atmosphere at 1325℃ for 2 hours to obtain a primary sintered body having a composition of TiO2:Y2O3:ZrO2=0.1:0.09:0.81 (molar ratio). The primary sintered body obtained had a relative density of 90% or more, an average grain size of 2μm or less, and a mixed crystal phase of cubic and tetragonal crystals.
[0149] The obtained primary sintered body was placed in a carbon container with a lid, and the carbon container was placed in a HIP device equipped with a carbon heating element. After that, a HIP-treated body was obtained by HIP-treating in a weakly reducing atmosphere under the following conditions.
[0150] Pressure medium: Argon gas (purity: 99.9%) Holding temperature: 1500℃ Holding pressure: 150MPa Holding time: 1 hour After that, the temperature was lowered to 1000°C at a rate of 80°C / min.
[0151] The HIP-treated body was heat-treated in an air atmosphere at 1000°C for 2 hours to obtain a sintered body of this comparative example made of titanium and yttrium-doped zirconia with an yttrium content of 9 mol% and a titanium content of 10 mol%. The sintered body of this comparative example was a cubic zirconia sintered body made of cubic crystal grains, and had a crystallite diameter of 1409 nm.
[0152] The results of the examples and comparative examples are shown in the table below. The compositions in the table below are calculated as oxides.
[0153] [Table 1]
[0154] All of the sintered bodies of the examples had high transparency with an It content of 50% or more, and had strength of 280 MPa or more. Furthermore, the sintered bodies of the examples had a fracture toughness value of 1.5 MPa m 0.5 Above 2.2MPa m 0.5From the above, it was confirmed that the sintered bodies had both high transparency and high resistance to the progression of fracture. Furthermore, all of the sintered bodies of the Examples had a peak with a peak top at 2θ=74.0±0.3°, and did not have a peak with a peak top at 2θ=72.8±0.3° or a peak with a peak top at 2θ=74.8±0.3°. On the other hand, the sintered bodies of Comparative Examples 3 and 4 had translucency but no transparency, and the fracture toughness value of the sintered body of Comparative Example 5 was 1.4 MPa m 0.5 It was confirmed that, although the It and three-point bending strength were high, the resistance to high fracture propagation was about half that of the example.
[0155] Example 5 The zirconia slurry and the titania slurry were mixed so that the mass ratio of the zirconia powder to the titania powder was 93:7, and a mixed slurry containing yttrium-stabilized zirconia powder containing alumina and titania was obtained, with the yttrium content being 4.75 mol%, the aluminum content being 0.047 mol%, and the titania content being 7 mol% (10.82 mol%). The sintered body of this example was made of titanium and yttrium-doped zirconia containing alumina, with the yttrium content being 4.75 mol%, the titanium content being 10.82 mol%, and the alumina content being 0.047 mol%. The measured density of the obtained primary sintered body was 5.84 g / cm. 3 The sintered body of this example had an average crystal grain size of 18 μm and a crystallite size of 693 nm.
[0156] Example 6 The zirconia slurry and the titania slurry were mixed so that the mass ratio of the zirconia powder to the titania powder was 94:6, and a mixed slurry containing yttrium-stabilized zirconia powder containing alumina and titania was obtained, with the yttrium content being 4.83 mol%, the aluminum content being 0.047 mass%, and the titania content being 6 mass% (9.33 mol%). In the same manner as in Example 1, except that, a sintered body of this example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with the yttrium content being 4.83 mol%, the titanium content being 9.33 mol%, and the alumina content being 0.047 mass%. The measured density of the obtained primary sintered body was 5.85 g / cm. 3 The sintered body of this example had an average crystal grain size of 15 μm and a crystallite size of 584 nm.
[0157] Example 7 A powder of yttrium-stabilized zirconia containing alumina, with an yttrium content of 5.0 mol% and an aluminum content of 0.05 mass%, was mixed with pure water. After mixing, the mixture was wet-pulverized in a ball mill until the average particle size was 0.5 μm and the standard deviation of the particle size was 0.1 μm, to obtain a zirconia slurry with a powder content (solid content concentration) of 45 mass%. A sintered body of this example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.35 mol%, titanium content of 12.26 mol%, and alumina content of 0.046 mass%, by the same method as in Example 1, except that the obtained zirconia slurry was used. The measured density of the obtained primary sintered body was 5.84 g / cm 3 The sintered body of this example had a crystallite diameter of 312 nm.
[0158] Example 8 A powder of yttrium-stabilized zirconia containing alumina, with an yttrium content of 6.5 mol% and an aluminum content of 0.05 mass%, was mixed with pure water. After mixing, the mixture was wet-pulverized in a ball mill until the average particle size was 0.5 μm and the standard deviation of the particle size was 0.1 μm, to obtain a zirconia slurry with a powder content (solid content concentration) of 45 mass%. A sintered body of this example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 5.65 mol%, titanium content of 12.39 mol%, and alumina content of 0.046 mass%, in the same manner as in Example 1, except that the obtained zirconia slurry was used. The measured density of the obtained primary sintered body was 5.84 g / cm 3 The sintered body of this example had a crystallite diameter of 1039 nm.
[0159] Example 9 A sintered body of this example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, with an yttrium content of 4.52 mol%, titanium content of 15.18 mol%, and alumina content of 0.045 mass%, in the same manner as in Example 1, except that the zirconia slurry and the titania slurry were mixed so that the mass ratio of the zirconia powder and the titania powder was 90:10. The measured density of the obtained primary sintered body was 5.81 g / cm. 3 The sintered body of this example had a crystallite diameter of 940 nm.
[0160] Example 10 A powder of yttrium-stabilized zirconia with an yttrium content of 5.5 mol% was mixed with pure water. After mixing, the mixture was wet-pulverized in a ball mill until the average particle size was 0.5 μm and the standard deviation of the particle size was 0.1 μm, to obtain a zirconia slurry with a powder content (solid content concentration) of 45 mass%. A sintered body of this example, made of titanium and yttrium-doped zirconia with an yttrium content of 4.67 mol% and a titanium content of 12.29 mol%, was obtained in the same manner as in Example 1, except that the obtained zirconia slurry was used. The measured density of the obtained primary sintered body was 5.84 g / cm 3 The sintered body of this example had a crystallite diameter of 781 nm.
[0161] Comparative Example 6 A powder of yttrium-stabilized zirconia containing alumina, with an yttrium content of 4.0 mol % and an aluminum content of 0.05 mass %, was mixed with pure water and wet-pulverized in a ball mill until the average particle size became 0.5 μm and the standard deviation of the particle size became 1.0 μm, to obtain a zirconia slurry with a solid content of 45 mass %.
[0162] The obtained zirconia slurry and titania slurry were mixed so that the mass ratio of zirconia powder to titania powder was 92:8, and a mixed slurry containing alumina and titania, in which the yttrium content was 3.40 mol%, the aluminum content was 0.046 mass%, and the titania content was 8 mass% (0.23 mol%), was obtained. In the same manner as in Example 1, except that, a sintered body of this comparative example was obtained, which is made of titanium and yttrium-doped zirconia containing alumina, in which the yttrium content was 3.40 mol%, the titanium content was 0.23 mol%, and the alumina content was 0.046 mass%. The sintered body of this comparative example had a crystallite diameter of 223 nm.
[0163] Comparative Example 7 The zirconia slurry and the titania slurry were mixed so that the mass ratio of the zirconia powder to the titania powder was 87.5:12.5, and a mixed slurry containing yttrium-stabilized zirconia powder containing alumina and titania, with the yttrium content being 4.33 mol%, the aluminum content being 0.044 mass%, and the titania content being 12.5 mass% (18.71 mol%), was obtained. Primary sintering, HIP treatment, and heat treatment were performed in the same manner as in Example 1, except that the mixed slurry containing yttrium-stabilized zirconia powder containing alumina and titania was obtained.
[0164] However, in this comparative example, cracks occurred during the heat treatment after the HIP treatment, and a sintered body could not be obtained.
[0165] The results are shown in the table below. The compositions in the table below are calculated as oxides. In addition, in Comparative Example 7, cracks occurred during the heat treatment and a sintered body was not obtained, so that it was not possible to evaluate Tt, etc.
[0166] [Table 2]
[0167] It was confirmed that, with the decrease in titanium content, It decreased, while Tt had no particular tendency. It was also confirmed that, with the decrease in titanium content, the fracture toughness value tended to improve. It was also confirmed from Examples 1 and 10 that, while the inclusion of alumina increased bending strength, it had no effect on the fracture toughness value.
[0168] On the other hand, in the comparative examples, it was confirmed that when the titanium content exceeded 18.5 mol %, a sintered body could not be obtained.
[0169] Example 11 In the same manner as in Example 1, a granular powder of yttrium-stabilized zirconia containing alumina and titania was obtained, in which the amount of yttrium was 4.67 mol %, the amount of aluminum was 0.046 mass %, and the amount of titania was 8 mass %.
[0170] Alumina powder, iron oxide powder, cobalt oxide powder, 4 mol% yttria-containing zirconia powder and titania powder were wet mixed in an ethanol solvent using a ball mill with zirconia balls to obtain a mixed powder containing 2 mass% alumina, 0.4 mass% iron oxide and 0.3 mass% cobalt oxide, with the remainder being 4 mol% yttria and 4.5 wt% titania-containing zirconia. The mixed powder was dried at 110°C in air, and then sieved to obtain a black raw material powder.
[0171] A disk-shaped primary mold having a diameter of 25 mm and an uneven shape was filled with yttrium-stabilized zirconia granule powder, and uniaxially pressed at a pressure of 25 MPa to obtain a disk-shaped primary molded body having a thickness of 2 mm and a diameter of 25 mm, which was made of yttrium-stabilized zirconia granule powder. The primary molded body was placed in a disk-shaped secondary mold having a diameter of 50 mm so that the convex shape of the primary molded body was the upper surface. The black raw material powder was filled so that the entire upper surface of the primary molded body was covered. Then, the primary molded body was uniaxially pressed at a pressure of 50 MPa to obtain a secondary molded body in which the primary molded body and a molded body made of black raw material powder were laminated. The obtained secondary molded body was subjected to CIP treatment at a pressure of 200 MPa. As a result, a disk-shaped secondary molded body having a thickness of 3.5 mm and a diameter of 50 mm was obtained.
[0172] The obtained secondary molded body was subjected to primary sintering, HIP treatment and heat treatment in the same manner as in Example 1 to obtain a composite sintered body of this embodiment in which the transparent zirconia sintered body and the black zirconia (opaque zirconia) sintered body were sintered together. The It of the black zirconia sintered body was 0.5% or less.
[0173] Example 12 A composite sintered body of this embodiment in which a transparent zirconia sintered body and a black zirconia (opaque zirconia) sintered body are sintered together was obtained in the same manner as in Example 11, except that a granular powder of yttrium-stabilized zirconia containing alumina and titania, in which the yttrium content was 4.75 mol%, the aluminum content was 0.047 mass%, and the titania content was 7 mass% (10.82 mol%), obtained in the same manner as in Example 5, was used.
[0174] The biaxial bending strength of the obtained sintered composite body was measured according to the biaxial bending strength measurement method specified in ISO / DIS 6872. The results are shown in the table below.
[0175] [Table 3]
[0176] The biaxial bending strength of the compound sintered body of this example exceeded 500 MPa in all cases, confirming that the sintered body of this embodiment can be used as a member having high mechanical strength.
Claims
1. A sintered body of zirconia in which titanium and yttrium are dissolved, the sintered body having an yttrium content of 3.5 mol% or more and less than 6.0 mol% and a titanium content of 6.0 mol% or more and 18.5 mol% or less, and which is made of cubic crystal grains including tetragonal domains and has an average crystal grain size of 5 μm or more and 50 μm or less.
2. The sintered body of claim 1 comprising alumina.
3. 3. The sintered body according to claim 1, wherein the crystallite size calculated from the half-width of a peak having a peak top at 2θ=74.0±0.3° in the XRD pattern is 1,400 nm or less.
4. Fracture toughness value (K IC ) is 1.5MPa m 0.5 The sintered body according to claim 1 or 2.
5. 3. The sintered body according to claim 1, having a three-point bending strength of 280 MPa or more.
6. 2. A method for producing a sintered body according to claim 1, comprising: a primary sintering step of sintering a molded body, which contains a zirconia source, a yttrium source, and a titanium source, and has an yttrium content of 3.5 mol% or more and less than 6.0 mol%, and a titanium content of 6.0 mol% or more and 18.5 mol% or less, under atmospheric pressure in an oxidizing atmosphere at 1260°C or more to obtain a primary sintered body; a pressure sintering step of pressure sintering the primary sintered body under a reducing atmosphere at 1500°C or more to obtain a pressure-treated body; and a heat treatment step of heat-treating the pressure-treated body in an oxidizing atmosphere.
7. The method according to claim 6, wherein the molded body is a molded body obtained by a molding step of molding a raw material powder obtained by a mixing method of mixing a mixed raw material powder of a zirconia source and an yttrium source with a titanium source.
8. The measured density of the primary sintered body is 5.35 g / cm 3 6.00g / cm or more 3 The method according to claim 6 or 7, wherein:
9. The method according to claim 6 or 7, wherein the pressure sintering is a hot isostatic pressing process.
10. The method according to claim 6 or 7, wherein the reducing atmosphere is a weakly reducing atmosphere.
11. The method according to claim 6 or 7, wherein the temperature drop rate from the holding temperature to 1000° C. in the pressure sintering is 50° C. / min or more and 300° C. / min or less.
12. A member comprising the sintered body according to claim 1 or 2.
Citation Information
Patent Citations
Light transparent zirconia sintered body
JP1987091467A
Sintered zirconia and production thereof
JP1990199059A
Highly transparent zirconia sintered body
JP2011011970A
High-strength transparent zirconia sintered body
JP2011102227A
Light transmissive zirconia sintered body, manufacturing method therefor, and application therefor
JP2018002527A